1985
DOI: 10.3109/01658108509014426
|View full text |Cite
|
Sign up to set email alerts
|

The w.e.b.i.n.o. syndrome

Abstract: Bilateral, simultaneous visual loss usually indicates vertebral-basilar insufficiency. We report the case of a patient who experienced transient, bilateral, simultaneous, asymmetrical visual loss. Arteriography revealed flow-restrictive lesions in both internal carotid arteries. The most likely cause for this symptom is bilateral ophthalmic artery hypoperfusion distal to high-grade stenotic lesions of the internal carotid arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…These findings suggest that the vestibulo-ocular reflex is intact and that the ophthalmoplegia in this patient probably originated from a supranuclear lesion (12). McGettrick et al (1) have suggested that an oculomotor nucleus lesion accounts for the exotropia in patients with WEBINO, but Gonyea (3) reported that the oculomotor nucleus was not involved. The findings in our patient favor Gonyea's observation.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These findings suggest that the vestibulo-ocular reflex is intact and that the ophthalmoplegia in this patient probably originated from a supranuclear lesion (12). McGettrick et al (1) have suggested that an oculomotor nucleus lesion accounts for the exotropia in patients with WEBINO, but Gonyea (3) reported that the oculomotor nucleus was not involved. The findings in our patient favor Gonyea's observation.…”
Section: Discussionmentioning
confidence: 88%
“…As the lesions of PSP characteristically involve the pontine and midbrain tegmentum and those of WEBINO involve the same regions (1,10), the appearance of WEBINO in PSP is not surprising. Brain MRI for this patient did reveal atrophic changes in the midbrain tegmentum, a finding previously described in WEBINO (11).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[2][3][4][5][6] INO is a component of paralytic pontine exotropia and the one-and-a-half syndrome that result from more extensive lesions in the MLF and surrounding tissue. 1,[7][8][9][10] The term "wall-eyed" bilateral internuclear ophthalmoplegia (WEBINO), coined by Lubow, refers to those bilateral cases in which an exodeviation, often quite large, is present in primary gaze ( Figure 1A). 4 Patients with large bilateral INOs may fuse in primary gaze, showing minimal exodeviation on cross cover testing.…”
mentioning
confidence: 99%
“…Wall-eyed bilateral internuclear ophthalmoplaegia (WEBINO) is a rare neuro-ophthalmological condition characterised by dissociated abducting nystagmus, impaired convergence and supranuclear vertical gaze palsy 1 2. It is caused by a midbrain lesion damaging the bilateral medial longitudinal fasciculus and pretectum, which is supplied by the anteromedial perforators of the posterior cerebral artery 2…”
Section: Descriptionmentioning
confidence: 99%